Kedudukan Hukum Dalam Perbankan Syariah Pada Sistem Perbankan Nasional - Ridha, Irfan; Hamdi, Al Hilal; Azmy, Alfani Tiara; Restiamedy, Angga; Romaito, Anggi; Zamhar, Atika; Fasya, Arifa; Irawan, Budi; Sihombing, Thomas Hardianto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Â Parties involved in non-litigation have the ability to make choices that are not only limited to the provisions contained in the Elucidation to Article 55 paragraph (2) in Law Number 21 of 2008 concerning Sharia Banking. They can also choose other alternatives according to the agreement in the approved contract. Supervision of the implementation of Sharia Banking, apart from being carried out internally, is also carried out by independent supervisory institutions such as the Sharia Supervisory Board (DPS) and the National Sharia Council (DSN). Their main task is to ensure that Islamic banking reaches an ideal situation and protect the interests of Muslims. In addition, as a form of community participation, all Muslims have the responsibility to carry out supervision, both directly and indirectly, as an effort to promote the good and prevent the bad in the implementation of sharia banking, which is a key element in Islamic economics.